Trends in vertical farm designs. Towards a biodynamic approach? - Gian Luca Brunetti (Techne)
This paper provides an overview of the state of the art in vertical farming experiments that have explored alternative approaches to the prevailing model, which is currently oriented toward active control of nutrient solutions, microclimatic conditions, and lighting, and is often scarcely aware of urban relations. These experiments propose a natural approach as an alternative to the established model, emphasising the creation of elevated soils, closure of biological cycles, passive climate control, maximisation of natural lighting, and establishing relations with the surrounding context. This approach offers significant functional advantages over the prevailing model, including a reduction in overall environmental impacts and the rate of pathogens affecting plants.